Comparing small scale plasticity of copper-chromium nanolayered and alloyed thin films at elevated temperatures. (July 2015) - Raghavan, R.; Harzer, T.P.; Chawla, V.; Djaziri, S.; Phillipi, B.; Wehrs, J.; Wheeler, J.M.; Michler, J.; Dehm, G.
Abstract: The yield strengths and deformation mechanisms of Cu–Cr nanolayered and alloyed thin films were studied by microcompression testing at elevated temperatures. The mechanical response of the films with alternating layers of Cu and Cr with sub-100 nm interlayer thicknesses and alloyed films of the same average composition was compared to determine the role of the interfaces on deformation. Higher resistance to plastic flow at elevated temperatures was exhibited by the nanolayered films with smaller interlayer thickness among the layered films, while the alloyed film revealed an anomalous increase in strength with temperature exhibiting a deformation mechanism similar to the pure Cr film.